Synthesis of Cu(II)-Organophosphonate Framework with Predefined Void Spaces - Bulut, Aysun; Zorlu, Yunus; Kirpi, Erdogan; Cetinkaya, Ahmet; Worle, Michael; Beckmann, Jens; Yucesan, Gundog (AMER CHEMICAL SOC, 2015)
Here we report the first utilization of the novel methane tetra-p-phenylphosphonic acid (MTPPA) ligand for the preparation of metal complexes with Cu(II). The hydrothermal and solvothermal reactions of tetratopic MTPPA as a bridging ligand in conjunction with the square pyramidal {Cu(terpy)}(2+) and {Cu-2(pbterpy)}(4+), (where terpy = 2,2':6',2 ''-Terpyridine and pbterpy = 4',4 ''''-(1,4-Phenylene)-bis(2,2':6',2 ''-terpyridine)) as prefixed corner building units have produced one-dimensional [{Cu(terpy)}(2)(MTPPA-H-5) (MTPPA-H-6)]center dot(4.2H(2)O)(H3O) (1) and two-dimensional [{Cu-2(pbterpy)}MTPPA-H-4] (2), respectively. The structures were characterized by single crystal X-ray diffraction and TGA.
Keywords: METAL-ORGANIC FRAMEWORKS; SINGLE-CRYSTAL STRUCTURE; STRUCTURAL CONSEQUENCES; RETICULAR CHEMISTRY; LIGAND; DESIGN; OXIDES; FAMILY; Chemistry; Crystallography; Materials Science